Extrusion, Debinding and Sintering of a Commercial Pure Titanium Ink for Robocasting - Kashimbetova, Adelia; Tkachenko, Serhii; Slámečka, Karel; Remešová, Michaela; Klakurková, Lenka; Pavloušková, Zina; Čelko, Ladislav; Montufar Jimenez, Edgar Benjamin (Tanger, 2021)
Among additive manufacturing technologies, robocasting emerges as a versatile and an affordable method for processing metallic materials. However, the success and competitiveness of robocasting depend on the development of easy-to-process metallic inks that do not generate residues after debinding and production of high purity metallic parts.

Among additive manufacturing technologies, robocasting emerges as a versatile and an affordable method for processing metallic materials. However, the success and competitiveness of robocasting depend on the development of easy-to-process metallic inks that do not generate residues after debinding and production of high purity metallic parts.
Extrusion, Debinding and Sintering of a Commercial Pure Titanium Ink for Robocasting
Keywords: additive manufacturing; robocasting; titanium; debinding; sintering; additive manufacturing; robocasting; titanium; debinding; sintering